URBAN WASTE MANAGEMENT AS A GOVERNANCE CHALLENGE : POLICY IMPLEMENTATION AND ACTOR NETWORKS IN BATU CITY - Lestari, Asih Widi; Firdausi , Firman; Qorib, Fathul (Universitas 17 Agustus 1945 Surabaya, 2026)
Urban waste management remains a persistent governance challenge in rapidly developing cities, particularly those with tourism-driven economies. This study examines municipal solid waste management in Batu City, Indonesia, focusing on how local governance arrangements shape policy performance. The findings show that, despite the existence of local regulations aligned with national waste policy, implementation remains predominantly disposal-oriented and highly dependent on the Tlekung landfill. Upstream strategies, including waste reduction, segregation, and community-based waste banks, are weakly institutionalized, fragmented, and largely dependent on short-term projects rather than embedded governance mechanisms. These limitations are reinforced by constrained municipal budgets, uneven administrative capacity across governance levels, and the absence of stable coordination between government agencies, community groups, and private waste actors. Seasonal waste surges associated with tourism further strain existing service capacity and expose systemic vulnerabilities in local waste governance. This study highlights that the core challenge lies not in regulatory absence but in fragmented governance and limited cross-sectoral integration. Strengthening collaborative governance arrangements and institutionalizing community participation are essential to shift urban waste management in Batu City from disposal-centered practices toward more sustainable and resilient governance outcomes.